2018
DOI: 10.1007/s11356-018-2087-y
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent responses of soil bacterial, fungal and nitrifying communities to silver nano and micron particles

Abstract: The growing use of silver nanoparticles (AgNPs) is likely to result in increased environmental contamination. Although AgNPs have been reported to affect microbial communities in a range of ecosystems, there is still a lack of information concerning the effect of low concentrations of AgNPs on soil microbial community structures and functional groups involved in biogeochemical cycling. In this study, the concentration-dependent effects of AgNPs and silver micron particles (AgMPs) on bacterial and fungal commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 51 publications
5
14
0
1
Order By: Relevance
“…Furthermore, Schlich et al [77] and Samarajeewa et al [86] observed stimulatory effects with ionic and nanoparticulate silver to ammonia-oxidizing bacteria, which could be ascribed to hormone-like responses to low silver concentrations. By contrast, the stimulation of Bacteroidetes due to silver addition was in agreement with previous observations [52,69,70,97,98]. They exhibit silver resistance genes [78].…”
Section: Exposure Timesupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Schlich et al [77] and Samarajeewa et al [86] observed stimulatory effects with ionic and nanoparticulate silver to ammonia-oxidizing bacteria, which could be ascribed to hormone-like responses to low silver concentrations. By contrast, the stimulation of Bacteroidetes due to silver addition was in agreement with previous observations [52,69,70,97,98]. They exhibit silver resistance genes [78].…”
Section: Exposure Timesupporting
confidence: 92%
“…The soil microbial community is responsible for several soil ecosystem services, like the recycling of organic matter, the soil fertility and structure, the biogeochemical nutrient cycles, the toxin degradation and the pathogen control [49][50][51][52][53]. Especially bacteria are the main performer of functional processes, which are integral for maintenance of healthy soil environments [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect strengths were in general higher for Ag + compared to AgNP. Actually, Acidobacteria are known for their AgNP intolerance in soils [ 16 , 17 , 19 , 49 ]. Here, they were significantly stimulated after 1-day exposure to environmentally relevant concentration of 0.01 mg AgNP/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, analyses of the soil bacterial community composition after AgNP exposure were focused on phylum level. These revealed an AgNP intolerance by Acido - and Actinobacteria , whereas Proteobacteria and Bacteroidetes seemed to be unaffected or promoted by silver applications [ 16 – 19 ]. This might lead to devastating effects on acidobacterial driven organic carbon transformation [ 20 ] as well as on actinobacterial recycling of refractory biomaterials by decomposition and humus formation in soils [ 21 ].…”
Section: Introductionmentioning
confidence: 99%